Talent as an unintentional agent - Papageorgiou (Κωνσταντίνος Παπαγεωργίου) Konstantinos (Bioethica, 2015)
Unintentional exposure is a novel concept. No single person has coined the term. It mainly refers to substances and activities affecting individuals without their consent – be it informed or not. In the broader field of applied ethics in general, and of bioethics in particular, the scope of application extends from nutrition (GM, functional food), to pollution (chemical-, air-, light-, noise-, radioactive contamination etc.), climate change, embryo rights, drug side-effects (especially in regard to chemotherapy), radiation (e.g. food), Permissible Exposure Limits, education and (bio-)terrorism. In the discussion about talent and giftedness1 there are two main approaches or schools of thought. On one hand, talent is conceived as an exclusive agent, in that some individuals are born more capable than others. On the other hand, a different school of thought advocates the modification of body and mind of all individuals in order for them to achieve similar levels of high performance. In the first case, individuals are bound to their nature, while in the latter instance they are prisoners of their environment –two equivalent positions in terms of autonomy and freedom. The latter will be argued to be the case; as a result, a connection with unintentional exposure will be established.